PENERAPAN MODEL PEMBELAJARAN TIPE JIGSAW DALAM PEMBELAJARAN IPA DI SMP NEGERI 5 KOTA METRO - Budiarti Budiarti (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
Science is one of the most important subject in senior high school. Even though for SMPN 5 Metro students. Increasing learning result is the teacher responsibly. Every teacher hoped to motivate and increase the students learning result. So that, number of effort has been tried to fulfill this big job.SMPN 5 Metro is one of the junior high schools in Metro city. Base on the pre-survey data, the students learning result of science subject and their learning participation was still low. This problems caused by some factors, both internal and external factor has accured in learning process. The researcher tried to implement the JIGSAW type of learning cooperative model fo recovering this problem. After conducting the research by implementating JIGSAW type of learning cooperative model in science subject, the researcher found that the students learning result can be increased 36,34%. Whereas 46,66% of students can fulfill MMC 70, before treatment and 83% after treatmen. It was also about the students learning activities can be improved till 8,3%, from 73% up to 81,3% at the end of second cycle. It is mean that JIGSAW type of learning cooperative model can increase the students learning result and their learning activities effectively. This JIGSAW type of learning cooperative model can also be an alternative learning model in science instructional process.